Environmental pressures, tumor characteristics, and death rate in a female breast cancer cohort: a seven-years Bayesian survival analysis using cancer registry data from a contaminated area in Italy - Giannico, Orazio Valerio; Carone, Simona; Tanzarella, Margherita; Galluzzo, Claudia; Bruni, Antonella; Lagravinese, Giovanna Maria; Rashid, Ivan; Bisceglia, Lucia; Sardone, Rodolfo; Addabbo, Francesco; Minerba, Sante; Mincuzzi, Antonia (Frontiers in Public Health, 2024)
Introduction: In Taranto, Southern Italy, adverse impacts on environment and human health due to industrial installations have been studied. In literature, few associations were reported between environmental factors and breast cancer mortality in women with breast cancer. The aim of this study was to investigate the relationships between residence in areas with high environmental pressures, female breast cancer characteristics and death rate. Methods: Data from the Taranto Cancer Registry were used, including all women with invasive breast cancer diagnosed between 01/01/2015 and 31/12/2020 and with follow-up to 31/12/2021. Bayesian mixed-effed effects logistic and Cox regression models were fitted with the approach of iIntegrated nNested lLaplace aApproximations, adjusting for patients and disease characteristics. Results: A total of 10445 person-years were observed. Variables associated with higher death rate were residence in the cContaminated sSite of nNational iInterest (SIN) (